Apostasy Between Fiqh Siyasah and Human Rights: A Critical Study of the Status and Sanctions of Apostasy in Islamic Law - Saiful Amin; Fahmi Akhyar Al Farabi; Faruq Aziz Al-Amin (Program Studi Hukum Tata Negara, 2025)
Apostasy in Islam has long been a controversial and sensitive issue, revealing the ongoing tension between classical Islamic jurisprudence and contemporary human rights principles. Traditional fiqh, particularly within classical Islamic legal texts, often prescribes harsh punishments for apostates, including the death penalty. In contrast, modern human rights frameworks emphasize freedom of religion and belief as non-negotiable, fundamental human rights. This article seeks to critically examine the legal status and punishment of apostasy through the dual lenses of fiqh siyasah (Islamic political jurisprudence) and international human rights discourse, using a normative-contextual approach grounded in maqāṣid al-sharī'ah (the higher objectives of Islamic law). The research adopts a qualitative method with library research as the main data collection technique. The findings suggest that classical juristic rulings on apostasy were shaped more by political and security considerations than purely theological concerns, particularly during the formative periods of Islamic governance. Viewed through the maqāṣid lens, these laws can be reinterpreted to prioritize justice, public welfare, and individual freedom. This article argues that reformulating Islamic criminal law on apostasy in light of constitutional guarantees and universal human rights does not necessarily conflict with core Islamic teachings. Instead, it offers an opportunity to bridge religious tradition and contemporary legal norms while preserving the ethical foundations of Islam. Such a balanced approach is essential to uphold both religious integrity and human dignity in pluralistic societies today.